The Effect of Perceived Ease of Use, Perceived Usefulness and Task Technology Fit on The Willingness to Use the Silat Pusaka Application - Mellinda, Devi; Muhardi, Muhardi; Nurdin, Nurdin (Yayasan Gema Bina Nusantara, 2025)
This study aims to analyze the influence of perceived ease of use (PEOU), perceived usefulness (PU), and task-technology fit (TTF) on the willingness to use the Silat Pusaka application at UPTD Puskesmas Padasuka Bandung. The research method uses a quantitative approach with a survey of 225 respondents. Data were analyzed using multiple linear regression with t-test and F-test. The results show that PEOU, PU, and TTF significantly influence willingness to use both partially and simultaneously. The adjusted R square value of 0.802 indicates that the three independent variables explain 80.2% of the variance in willingness to use. Findings imply that ease of use, perceived benefits, and task alignment critically support successful adoption of health information systems in primary care services. Therefore, developers and management teams must prioritize user-friendly designs, demonstrate clear practical advantages, and ensure technology aligns effectively with healthcare workflows to enhance user acceptance and sustainable adoption in similar healthcare settings.